2019
DOI: 10.1002/slct.201803033
|View full text |Cite
|
Sign up to set email alerts
|

On the Adherence of Chemically Deposited CdS Films to Common Inorganic Substrates: Effect of Cd2+ Concentration in Solution, Substrate Surface Chemistry, and Reaction Temperature

Abstract: The bad adherence to the substrate of chemical-solutiondeposited chalcogenide films in alkaline solution is a current technological problem. However, this issue is belittled since is commonly solved by employing pre-sensitized substrates or by empirically changing the deposition parameters until "finding" the "proper" chemical formulation. For these reasons, the issue of the adherence has not been previously studied. The present research aims to properly discuss the issue of adherence by taking as example CdS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Examples of high‐reactivity sites in glasses, which are widely used as substrates, are those local environments created by the incorporation of tin atoms in the bottom side (tin‐bath side) of flat glasses when the glass ribbon is floated on molten tin during industrial production of float flat glasses (tin atoms are present in about 5.24 % of the surface atomic population, as was determined in a previous work [1] ). The upper side (atmosphere side) of such glasses, which is exposed to a reducing atmosphere during the float process, shows a very low content of tin atoms (tin atoms are present in 0.67 % of the surface atomic population, as was determined in a previous work [1] ), and therefore, it has a low number of high‐reactivity sites. This is the reason why a CdS thin film shows poor adhesion to the atmosphere side of float glass when the film is deposited from a low Cd 2+ reaction solution at reaction temperatures equal to and above 40 °C.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Examples of high‐reactivity sites in glasses, which are widely used as substrates, are those local environments created by the incorporation of tin atoms in the bottom side (tin‐bath side) of flat glasses when the glass ribbon is floated on molten tin during industrial production of float flat glasses (tin atoms are present in about 5.24 % of the surface atomic population, as was determined in a previous work [1] ). The upper side (atmosphere side) of such glasses, which is exposed to a reducing atmosphere during the float process, shows a very low content of tin atoms (tin atoms are present in 0.67 % of the surface atomic population, as was determined in a previous work [1] ), and therefore, it has a low number of high‐reactivity sites. This is the reason why a CdS thin film shows poor adhesion to the atmosphere side of float glass when the film is deposited from a low Cd 2+ reaction solution at reaction temperatures equal to and above 40 °C.…”
Section: Introductionmentioning
confidence: 76%
“…In a previous work, [1] we addressed for the first time the issue of adhesion of thin films deposited by a chemical solution technique to certain substrates. We found that, for the case of cadmium sulfide (CdS), which is still a very relevant semiconductor material, the adherence to a given substrate is improved by an increase in the concentration of cadmium salt or by a decrease in the reaction temperature; these parameters are operative factors related to the reaction solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations